Floating And Sinking - Sepehri, Sandy; Nang Chan Yeema (Los Angeles, California, United States Fitzgerald Books, 2007)
Text and photographs introduce the physical science of volume and density, including why some things sink while other things float.
Keywords: Juvenile Nonfiction